2022
DOI: 10.1530/ec-21-0309
|View full text |Cite
|
Sign up to set email alerts
|

Are patients with polycystic ovary syndrome more prone to irritable bowel syndrome?

Abstract: Background: Polycystic ovary syndrome (PCOS) encompasses endocrine, reproductive and metabolic disturbances. Abdominal pain and bowel movement disturbances are common complaints of PCOS patients. It remains uncertain whether the characteristic features of PCOS are associated with an increased incidence of irritable bowel syndrome (IBS). Methods: 133 patients with PCOS diagnosed according to international evidence-based guidelines and 72 age- and BMI-matched eumenorrheic controls were enrolled to the study. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…Sexual difficulties resulting from pain during intercourse are another major complaint of patients with PCOS [ 122 , 123 , 124 ], and they are typical symptoms of endometriosis. Relative to healthy individuals, patients with PCOS are more likely to develop chronic-pain-related and neuropathic-pain-related conditions such as migraine [ 27 ], fibromyalgia [ 107 ], rheumatoid arthritis [ 125 ], and irritable bowel syndrome [ 126 , 127 , 128 ]; thus, PCOS is a potential risk factor for the increased prevalence of pain-related conditions. However, the current HRQoL survey formats are limited in their ability to obtain comprehensive information regarding the pain perception of patients with PCOS.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Sexual difficulties resulting from pain during intercourse are another major complaint of patients with PCOS [ 122 , 123 , 124 ], and they are typical symptoms of endometriosis. Relative to healthy individuals, patients with PCOS are more likely to develop chronic-pain-related and neuropathic-pain-related conditions such as migraine [ 27 ], fibromyalgia [ 107 ], rheumatoid arthritis [ 125 ], and irritable bowel syndrome [ 126 , 127 , 128 ]; thus, PCOS is a potential risk factor for the increased prevalence of pain-related conditions. However, the current HRQoL survey formats are limited in their ability to obtain comprehensive information regarding the pain perception of patients with PCOS.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…All of these studies had moderate to high-quality score. In two studies, the prevalence of IBS was similar in women with PCOS compared with the controls [6,7]. The results of Kałużna et al's study showed that the prevalence of IBS symptoms in patients with PCOS was not different from that in the control group.…”
Section: Overview Of the Relationship Between Pcos And Ibsmentioning
confidence: 91%
“…All of these studies had moderate to high‐quality score. In two studies, the prevalence of IBS was similar in women with PCOS compared with the controls [ 6 , 7 ]. The results of Kałużna et al.…”
Section: Overview Of the Relationship Between Pcos ...mentioning
confidence: 99%
See 2 more Smart Citations